Abū al-Barakāt al-Baghdādī and His Use of Ibn Sīnā's al-Ḥikma al-‘Arūḍiyya (or another work closely related to it) in the Logical Part of His Kitāb al-Mu‘tabar - Jules Janssen (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
The last four sections of the first book of Abū al-Barakāt al-Baghdādī’s summa, entitled Kitāb al-Mu‘tabar, deal with dialectics, sophistical refutations, rhetoric, and poetics in full line with Aristotle’s Organon. However, they are not so much based on Aristotle’s works, but on a work of the young Ibn Sīnā, namely al-Hikma al-‘Arūdiyya. Both texts have much in common not only in their structure, but also in their very wording. The article presents a basic survey of the correspondences for all four sections and also highlights the most significant differences. However, important part of these differences has a counterpart in an (incomplete) logical text, which is present in the manuscript Nuruosmaniye 4894 and which is, in turn, very close to, albeit not identical, with Ibn Sīnā’s al-Hikma al-‘Arūdiyya as conserved in the unique manuscript Uppsala 364. Therefore, it is obvious that Abū al-Barakāt takes over many formulations and, at once, many ideas from Ibn Sīnā. However, he adds clearly personal elements that often seem to have been religiously inspired and, on occasion, consciously returns to Aristotle’s wording.